Pengaruh current ratio (CR) dan return on equity (ROE) terhadap harga saham - Syafira, Erika Anggita; Hendayana, Yana (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The purpose of this study was to analyze the effect of Current Ratio (CR) and Return on Equity (ROE) on Stock Prices on construction subsector companies listed on the Indonesia Stock Exchange (IDX) 2014-2019. The research method used is descriptive verification method. The study population consists 19 companies with a total sample of 12 companies selected using purposive sampling technique. This study uses panel data regression that is processed with Eviews 9 to determine the influence of each independent variable on stock prices. The results showed together that Current Ratio (CR) and Return on Equity (ROE) had a linier relationship with the Stock Price. Partially the results of the study indicate that Return on Equity (ROE) affects the Stock Price. While Current Ratio (CR) don’t have effect on stock prices.